Protocol used for AFLP by automatic laser fluorescence analysis - Nataša ŠTAJNER; Branka JAVORNIK; Dunja BANDELJ (Acta Agriculturae Slovenica)
The AFLP (amplified fragment length polymorphism) technique using fluorescence-labelled primers and automated detection is described and some features of this method are discussed. The modified AFLP technique is suitable for efficient fingerprinting analysis and gives a much higher resolution than silver staining detection systems. With the aid of an automated ALFexpress sequencer and computer software, the AFLP method is much considerably easier to perform and the total time required is reduced.